Key competencies of students with autism spectrum disorders: Perspectives of Chinese teachers and parents - Cao, Shuqin; Wang, Yixin; Yang, Xiaofang; Jin, Qiqin; Hui-Michael, Ying; Xie, Dongjie (Frontiers in Psychology, 2022)
Well-defined key competencies for students with autism spectrum disorders (ASD) help develop curriculum and pedagogies that emphasize what students with ASD are expected to learn, to know and to do. Most of the current research on the key competencies of ASD is theoretical and based on the social and cultural backgrounds of western countries. The key competencies defined by most of the research lack of the support of empirical evidence. This study sought to identify the key competencies of school-age students with ASD from the perspectives of teachers and parents. Based on the review of existing key competencies frameworks, a key competencies instrument that consisted of 76 learning outcome items in eight domain areas was developed. An online survey to explore the teachers’ and parents’ views of the key competencies was conducted with 1618 teachers and 2430 parents of students with ASD across China. The results showed that teachers believed that the key competencies should consist of eight domain areas including social-communication, learning skills, healthy living, play, motor, emotion, sensory processing, and cognition, while the cognition related competencies were not recognized by parents. The competencies in social-communication, learning skills, healthy living had higher variance contribution. From the perspective of teachers, the variance contribution of social communication was the highest, while from the perspective of parents, the variance contribution of learning skills was the largest. Taken together, the key competencies framework for students with ASD should include eight dimensions and 75 learning outcome items. The findings could provide empirical data to assist in developing educational guidelines and guide the development of models of support for students with ASD.